PEDESTRIAN ROBOT - Shut’, Vasilij (International Journal of Computing, 2014)
In the paper there are analyzes the major drawback of pedestrian crossings, namely, interruption of vehicles moving flow on the highway. It is given a calculation of economic losses in the conflict “pedestrian-vehicle” on a controlled pedestrian crossing. It is proposed a radical solution of this problem by setting the bus system “Walking Robot”, which quickly and safely move pedestrians to the opposite side of the highway with minimal disruption of a highway traffic flow.